2017
DOI: 10.1186/s40662-017-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, fellow eye, comparison of keratometry, aberrometry, tear film, axial length and the anterior chamber depth after eye rubbing in non-keratoconic eyes

Abstract: BackgroundTo investigate the effect of eye rubbing on keratometry (K), aberrometry, tear film break-up-time (TFBUT) and anterior chamber depth (ACD).MethodsVolunteers without any corneal pathology or dry eyes were randomised to rubbing in one eye and the fellow-eye was control. Eye rubbing was performed for 2 min. Primary outcomes studied were anterior and posterior K changes. Secondary outcomes were changes in TFBUT, axial length (AL) & ACD, K changes in various zones, asphericity and aberrometry. Pre and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…Previous studies suggest that eye rubbing is associated with a spectrum of changes ranging from transient against-the-rule astigmatism to transient ectasialike corneal changes, which may develop over time into real keratoconus. [5][6][7][8][9][10] In their overview of managing chronic eye rubbing, McMonnies et al 23 discussed the possible factors associated with such a behavior regardless of a coexisting psychopathology. Such factors include learning disturbances, sleep prob-lems, and habit reactions, all of which may lead to increased stress in the affected person.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggest that eye rubbing is associated with a spectrum of changes ranging from transient against-the-rule astigmatism to transient ectasialike corneal changes, which may develop over time into real keratoconus. [5][6][7][8][9][10] In their overview of managing chronic eye rubbing, McMonnies et al 23 discussed the possible factors associated with such a behavior regardless of a coexisting psychopathology. Such factors include learning disturbances, sleep prob-lems, and habit reactions, all of which may lead to increased stress in the affected person.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive mechanical irritation of the corneal surface has been shown to be a major risk factor for both disease occurrence and progression . Recurrent eye rubbing has been shown to cause transient ectasia-like corneal changes, which may transform into true keratoconus if mechanical irritation continues …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al concluded that tear film disruption makes the optical surface irregular and may cause aberrations or unpredictable keratometry measurements [37]. Additionally, Chervenkoff et al reported a significant change in central anterior K readings in healthy eyes following eye rubbing [38].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that eye rubbing induces changes in epithelial thickness, tear film, and keratometry. 29,30 However, until now, it has not been possible to prove that keratoconic topographic alterations are due to the effects of eye rubbing or to intrinsic disease.…”
Section: Discussionmentioning
confidence: 99%